Private sector extension services get (climate) smart: Coffee in Uganda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The Stepwise Climate Smart Investment Pathway is an approach developed by IITA in collaboration with partners. Stepwise breaks down the recommended best practices that many farmers cannot afford to implement into smaller, more affordable packages that can be implemented in phases. Stepwise considers specific agro-ecological variables and farmer needs and aspirations to guide incremental investment by the farmer in specific sets of, and timing of practices. This incremental investment is expected to subsequently increase coffee yields in a stepwise manner.